1979
DOI: 10.1063/1.438597
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical determination of the electron affinity of the ethynyl radical, HC2⋅

Abstract: The cross section for electron photodetachment has been measured for the acetylide anion (HC2−) using an ion cyclotron resonance spectrometer in conjunction with a xenon arc lamp. Calculation of the photodetachment behavior near threshold and an estimate of the Franck–Condon factors for the anion→neutral transition allow us to determine EA (HC2⋅) = 2.94±0.10 eV. A theoretical determination using eighth-order perturbation theory gives an adiabatic electron affinity of 3.18±0.25 eV, in good agreement with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 24 publications
8
22
1
Order By: Relevance
“…al. 8 have come up with a value for Do(C 2 H-H) of 132*5 kcal/mol by combining processes VIII, IX and X in a thernochemical cycle. This result is in good agreement with the present work although the uncertainty is still fairly large.…”
Section: Results and Analysismentioning
confidence: 99%
“…al. 8 have come up with a value for Do(C 2 H-H) of 132*5 kcal/mol by combining processes VIII, IX and X in a thernochemical cycle. This result is in good agreement with the present work although the uncertainty is still fairly large.…”
Section: Results and Analysismentioning
confidence: 99%
“…All these experimental and theoretical details confirmed that CH 3 S and CH 3 S 2 are the products of the photodissociation. In comparison with the CH 3 S3, 11–21 radical, much less known about CH 3 S 2 radical, mainly because of its low stability and spontaneously dissociates to form slow S 2 and CH 3 radical. In 1990, the CH 3 S 2 radical from CH 3 SSCH 3 , was first detected by Nourbakhsh et al4 using translational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…At this level of calculation, it may be seen that the difference between the vertical and adiabatic EAS of HC, is very mild. Zero-point vibrational correction is known to be comparable or even less significant [3,8]. The thermodynamic and photodetachment energies are calculated to have only a minor difference.…”
Section: Resultsmentioning
confidence: 99%